The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/15412555.2017.1379070
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Adherence to Pulmonary Rehabilitation for Chronic Obstructive Pulmonary Disease

Abstract: Adherence to pulmonary rehabilitation (PR) is low. Previous studies have focused on clinical predictors of PR completion. We aimed to identify social determinants of adherence to PR. A cross-sectional analysis of a database of COPD patients (N = 455) in an outpatient PR program was performed. Adherence, a ratio of attended-to-prescribed sessions, was coded as low (<35%), moderate (35-85%), and high (>85%). Individual-level measures included age, sex, race, BMI, smoking status, pack-years, baseline 6-minute wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 61 publications
(55 reference statements)
4
44
0
13
Order By: Relevance
“…Regarding the education level, the same previous study showed that education had no effect on adherence of PR [12]. In contrast to a recent prospective study which demonstrated that patients with lower levels of education would have more likely to drop out or did not attend the program [32], Oates et al recently indicated that moderate adherence was associated with socioeconomic disadvantage, for example, the income level, unemployment rate, and the number of household vehicles, and the low adherence was associated with limited function [33].…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the education level, the same previous study showed that education had no effect on adherence of PR [12]. In contrast to a recent prospective study which demonstrated that patients with lower levels of education would have more likely to drop out or did not attend the program [32], Oates et al recently indicated that moderate adherence was associated with socioeconomic disadvantage, for example, the income level, unemployment rate, and the number of household vehicles, and the low adherence was associated with limited function [33].…”
Section: Discussionmentioning
confidence: 89%
“…Given that PR resources are limited, selection of candidates for PR who are likely to adhere to and complete the programme is an important consideration. In studies conducted to date, current smoking, depression, social isolation, poor mobility, lack of perceived benefit, extremes of age, dyspnoea severity, long‐term oxygen therapy, transportation difficulty or travel distance, socio‐economic disadvantage and costs have been associated with non‐adherence and/or lack of programme completion . Despite these associations, many complex factors influence uptake, adherence to and completion of PR, and no individual adherence‐related parameters can be used reliably to predict consistently which people will complete the programme, hence patient candidacy for PR should not presently be based on these factors.…”
Section: Additional Considerations For Patient Selection For Prmentioning
confidence: 99%
“…Knowledge of and skills in the field of SDH can support physicians in their everyday practice, for example, by improving the understanding of patients' adherence to particular treatment regimens. [10][11][12] Acknowledging the importance of SDH, the WHO Commission on SDH (CSDH) emphasises the necessity and advantage of a SDH-framed mind-set for health professionals. It recommends that SDH should be a standard and compulsory part of the training of medical students and other health professionals.…”
Section: Introductionmentioning
confidence: 99%